Communication practices of parents and unaffected sibling needs in families impacted by a diagnosis of Angelman syndrome. Issue 7 (1st April 2022) - Turnwald, Abigail; Thompson, Talia; Nori, Kelly; Duis, Jessica
Abstract: Angelman syndrome (AS) is a rare neurodevelopmental condition affecting approximately 1 in 15, 000 individuals. To date, limited research elucidates how parents communicate about AS with unaffected siblings and their needs. This study aimed to understand if, when, and what parents are communicating with unaffected siblings. The study also evaluated unaffected siblings' knowledge of AS and their perceptions of their siblings with AS. Recruitment took place through social media platforms and a multidisciplinary Chromosome 15 clinic. Families were eligible for the study if they had a child diagnosed with AS and at least one unaffected sibling age five years or older. Two novel surveys, one for the parent and one for each of the unaffected siblings, were created based on a detailed literature review and input from AS professionals. Eighty‐two families met the criteria and completed the required surveys. The majority of parents (94%) discussed AS with the unaffected siblings, but despite these discussions 41% of unaffected siblings still had unanswered questions. This study highlights the need for improved communication between parents and the unaffected siblings and emphasizes the importance of educational materials for unaffected siblings.